Divided communities and contested landscapes: Mobility, development and shifting identities in migrant destination sites in Papua New Guinea - Koczberski, Gina; Curry, George (2004)
Internal conflicts at the local and national levels in several South Pacific countries have revealed the fragility of national unity and the difficulties nations face in governing and managing their own economic development. In Papua New Guinea, the focus of this paper, an uncertain economic future for many rural and urban communities, and rising inequalities in income opportunities and access to resources, have coincided with greater intolerance of migrants at sites of high in-migration by customary landowners and provincial and local authorities. This paper draws on fieldwork undertaken in the major oil palm growing regions of Papua New Guinea where migrants from densely populated regions of the country have settled on state land alienated from customary landowners. We examine how struggles over land, resource control and development are polarising migrant and landowner identities resulting in increasing tensions and episodic communal violence. A settler identity is emerging based on a narrative of nation building and national development, while an ethno-regional identity amongst customary landowners is undermining the citizen rights of migrants and challenging the role and authority of the state in land matters.